A review on laser and light-based therapies for alopecia areata. (17th February 2017) - Mlacker, Stephanie; Aldahan, Adam Souhail; Simmons, Brian James; Shah, Vidhi; McNamara, Colin Andrew; Samarkandy, Sahal; Nouri, keyvan
ABSTRACT: Alopecia areata is a form of non-scarring alopecia that results from a hyperactive immune response of T cells against hair follicles. Many patients with visible hair loss experience psychological and emotional distress, as a result of their cosmetic disfigurement, and frequently seek treatment. However, existing treatment methods, such as corticosteroids, topical irritants, sensitizing agents, immunosuppressants, and psoralen plus ultraviolet light A, may result in various adverse effects and often lack efficacy. Laser and light treatments offer a safe and effective alternative. This review aims to provide clinicians with a comprehensive summary of laser and light-based modalities used for the treatment of alopecia areata. Currently, the excimer laser is the most widely studied device and has shown positive results thus far. However, the development of future randomized controlled clinical trials will help determine the appropriate treatment protocols necessary, in order to achieve superior clinical outcomes.